2023
DOI: 10.1002/smtd.202300833
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Impact of Mechanochemical Treatment on the Na‐ion Conductivity of Sodium Closo‐Carbadodecaborate Probed by X‐Ray Raman Scattering Spectroscopy

Valerio Gulino,
Alessandro Longo,
Laura M. de Kort
et al.

Abstract: Solid‐state sodium ion conductors are crucial for the next generation of all‐solid‐state sodium batteries with high capacity, low cost, and improved safety. Sodium closo‐carbadodecaborate (NaCB11H12) is an attractive Na‐ion conductor owing to its high thermal, electrochemical, and interfacial stability. Mechanical milling has recently been shown to increase conductivity by five orders of magnitude at room temperature, making it appealing for application in all‐solid‐state sodium batteries. Intriguingly, millin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Ball milling has also been well recognized as a means of introducing defects that are considered advantageous for enhancing ion conductivity in many solid electrolytes. Promoting perturbation in solid crystals is a widely recognized approach that serves to stabilize non-equilibrium phases in diverse materials or facilitate the formation of structural flaws [127,260].…”
Section: Mechanochemical Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ball milling has also been well recognized as a means of introducing defects that are considered advantageous for enhancing ion conductivity in many solid electrolytes. Promoting perturbation in solid crystals is a widely recognized approach that serves to stabilize non-equilibrium phases in diverse materials or facilitate the formation of structural flaws [127,260].…”
Section: Mechanochemical Techniquesmentioning
confidence: 99%
“…Lately, mixing/milling techniques have been widely used in the mechanochemical synthesis of solid electrolytes and the processing of cathode composites, e.g., the preparation of functional composite materials and the production of ASSB components, even at a large scale [16,24,29,36,78,85,[117][118][119][120][121][122][123][124][125][126]. Recent studies have demonstrated that mechanical milling has the potential to significantly enhance conductivity by five orders of magnitude at ambient temperature; this remarkable improvement renders mechanical milling an attractive technique for utilization in ASSBs [127]. It is also well known that composite formation can have a great impact on electrode performance [128][129][130][131][132][133][134].…”
Section: Introductionmentioning
confidence: 99%